EXPLORING NEW FRONTIERS: A CASE STUDY IN CORPORATE EDUCATION AND ACCESSIBLE COMMUNICATION AT COACH ITCONSULTING IN IT - Botechia, Ariadne [UNESP] (2024)
This article analyzes a case study carried out in 2022 at Coach It - IT Consulting, in Sorocaba, addressing the implementation of innovative corporate education practices and accessible communication strategies. We explore the interconnections between corporate education, accessible communication, and the specific demands of the IT sector in the critical literature review. The methodology of the case study, followed by the results and analyses, is presented. The conclusion highlights key findings, closing with reflections on the contributions to the fields of corporate education and accessible communication. This study aims to enrich the understanding of how companies can align corporate learning strategies with the promotion of inclusion, contributing to more adaptive and equitable organizational environments.